National Culture, Economic Development, Population Growth and Environmental Performance: The Mediating Role of Education - Peng, Yu-Shu (Journal of business ethics, 2009)
Literature on ethical behavior has paid little attention to the mechanism between macro- environmental variables and environmental performance. This study aims at constructing a model to examine the␣relationships which link cultural values, population growth, economic development, and environmental performance by incorporating the mediating role of education. The multiple linear regression model was employed to test the hypotheses on a 3-year-pooled sample of 51 countries. Empirical results conclude that national culture, economic development, and population growth would significantly influence environmental performance directly. In addition, through the mediating effect of education, population growth and national culture would significantly affect environmental performance indirectly. These findings provide theoretical and managerial implications for constructing the mechanism of cultural values and ethical behavior in general and environmental management in particular.